Lack of a Dose Response from 7 Days of Ischemic Preconditioning in Moderately trained Cyclists - Lindsay, Angus; Petersen, Carl; Ferguson, Hamish; Blackwell, Gavin; Rickerby, Stephen (Sports Medicine International Open, 2018)
Ischemic preconditioning (IP) has a small benefit on exercise performance, but differences in the IP method, performance tasks and exercise modality have made providing practical coach guidelines difficult. We investigated the performance-enhancing effects of IP on cyclists by comparing the frequency of IP application over a 7-day period. Using a randomized, sham-controlled, single-blinded experiment, 24 competitive age-group track cyclists (38±12 years) were assigned to one of three twice-daily (sham: 20 and 20 mmHg; once-a-day: 20 and 220 mmHg; twice-a-day: 220 and 220 mmHg) IP leg protocols (4 × 5 min ischemia/5 min reperfusion alternating between legs) over seven consecutive days. A 4000-m cycling-ergometer time trial was completed before, immediately following and one week after the protocols. Neither mean power, nor 4000-m performance time nor VO2 were significantly affected by either of the IP protocols compared to the sham at any time point following treatment. Repeated application of IP over seven days did not enhance the performance of trained cyclists in a 4000-m laboratory time trial. More research is required to understand how changes to methodological variables can improve the chances of IP successfully enhancing athlete performance.
Keywords: time trial; hypoxia; occlusion; reperfusion; sport